Pengembangan Modul Praktikum Instalasi Penerangan Listrik di SMK Negeri 1 Talaud - Malado, Janles; Habibu, Christy Oktaviani (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
This research is a type of research and development The purpose of this research is to develop a practicum module on the subject of electric lighting installation at SMKN 1 Talaud The stages carried out in this research are through five stages namely: i analysis; ii design; iii development; iv implementation; and v evaluation The final assessment of the feasibility of this practicum module obtained the following results: i a score from the material expert was 100 ; ii the first design expert score was 98 ; iii the second design expert score was 94 ; and iv the user rating score was 98 3 From the assessment results the electric lighting installation practicum module is feasible to use < strong>< p>